Respuesta :

Answer: OPTION C

Given the functions shown in the figure attached, you have that f(x)*g(x), means that you must multiply both functions.

Therefore, you have:

[tex]f(x)*g(x)=(12x^{2}-6x)(2x)[/tex]

Now, you must apply the distributive property, therefore, you obtain:

[tex]f(x)*g(x)=24x^{3}-12x^{2}[/tex]

As you can see, the answer is the Option C.

Answer:

[tex]f(x)\times g(x)=24x^3 -12x^2[/tex]

Step-by-step explanation:

The given functions are

[tex]f(x)=12x^2-6x[/tex]

and

[tex]g(x)=2x[/tex]

[tex]f(x)\times g(x)=(12x^2-6x)\times 2x[/tex]

We expand using the distributive property to obtain;

[tex]f(x)\times g(x)=12x^2\times 2x-6x\times 2x[/tex]

This simplifies to;

[tex]f(x)\times g(x)=24x^3 -12x^2[/tex]

The correct answer is C

ACCESS MORE